Effect of Biomass Drying Protocols on Bioactive Compounds and Antioxidant and Enzymatic Activities of Red Macroalga Kappaphycus alvarezii - Nunes, Aline [UNESP]; Dutra, Felipe de Souza; Brito, Sinara de Nazaré Santana [UNESP]; Pereira-Vasques, Milene Stefani [UNESP]; Azevedo, Gadiel Zilto; Schneider, Alex Ricardo; Oliveira, Eva Regina; Santos, Alex Alves dos; Maraschin, Marcelo; Vianello, Fábio; Lima, Giuseppina Pace Pereira [UNESP] (MDPI, 2024)
Kappaphycus alvarezii is a red seaweed used globally in various biotechnological processes. To ensure the content and stability of its bioactive compounds postharvest, suitable drying protocols must be adopted to provide high-quality raw materials for industrial use. This study aimed to analyze the influence of freeze-drying and oven-drying on the total phenolic content (TPC), total flavonoid content (TFC), antioxidant activity (FRAP and DPPH assays), total carotenoid content (TC), and lipase (LA) and protease activity (PA) of K. alvarezii samples collected over the seasons in sea farms in southern Brazil. The freeze-drying technique was found to be more effective regarding superior contents of TPC (39.23 to 127.74 mg GAE/100 g) and TC (10.27 to 75.33 μg/g), as well as DPPH (6.12 to 8.91 mg/100 g). In turn, oven-drying proved to be the best method regarding the TFC (4.99 to 12.29 mg QE/100 g) and PA (119.50 to 1485.09 U/g), with better performance in the FRAP (0.28 to 0.70 mmol/100 g). In this way, it appears that the drying process of the algal biomass can be selected depending on the required traits of the biomass for the intended industrial application. In terms of cost-effectiveness, drying the biomass using oven-drying can be considered appropriate.
Keywords: antioxidants; enzymes; freeze-dried; oven-dried; phenolic compounds; seasonality